1974
DOI: 10.1128/aac.5.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Cefoxitin, a Semisynthetic Cephamycin Antibiotic: Resistance to Beta-Lactamase Inactivation

Abstract: Cefoxitin is a new, cephalosporin-like antibiotic which is highly resistant to hydrolysis by #-lactamase. Ninety-one cultures were selected either for their general resistance to cephalosporin antibiotics or for their ability to produce f-lactamase. Some of these cultures were resistant to cefoxitin. The capacity of each of the 91 strains to hydrolyze cefoxitin with fi-lactamase was determined. Only seven of the cultures degraded the antibiotic as determined by a general assay for fi-lactamase. Several others … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
81
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(84 citation statements)
references
References 20 publications
3
81
0
Order By: Relevance
“…The latter may be represented as alteration of bacterial permeability to the antibiotics. Since many ,8-lactam antibiotics resistant to hydrolysis by ,8-lactamases have been developed recently (5,7,17), it is possible that mutants acquiring resistance mechanisms other than ,8-lactamase production selectively appear. In fact, Medeirous et al (14) presented some evidence that the resistance of a few strains of Escherichia coli to ampicillin and to carbenicillin was due to their low permeability for the antibiotics.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The latter may be represented as alteration of bacterial permeability to the antibiotics. Since many ,8-lactam antibiotics resistant to hydrolysis by ,8-lactamases have been developed recently (5,7,17), it is possible that mutants acquiring resistance mechanisms other than ,8-lactamase production selectively appear. In fact, Medeirous et al (14) presented some evidence that the resistance of a few strains of Escherichia coli to ampicillin and to carbenicillin was due to their low permeability for the antibiotics.…”
mentioning
confidence: 99%
“…In fact, it has become evident that ,8-lactamase activities of microorganisms playa role in their resistance to cephalosporins and penicillins (17,19,22,25,29). However, there is some evidence that bacterial resistance to the antibiotics does not necessarily correlate with the enzyme activity (17,28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cefoxitin, a thienylacetyl derivative of deacetyl-3-0-carbamoyl-7-a-methoxycephalosporin C, has been reported to have activity against grampositive and gram-negative organisms (21). This 7-methoxylated cephalosporin generally showed resistance to the action of beta-lactamases from both gram-positive and gram-negative bacteria (14), and it was suggested that this characteristic contributed to the broad antimicrobial spectrum observed. There is considerable disagreement as to the relative importance of beta-lactamases in bacterial resistance to beta-lactam antibiotics (20).…”
mentioning
confidence: 99%
“…This parenteral drug is a representative of a newer group of cephalosporin antibiotics which shows relative resistance to beta-lactamases of gram-negative bacilli. This group includes cefoxitin, cefamandole (CFM), cefuroxime, and ceforanide (CFN) (7)(8)(9)(10)(11)13). Due in part to this resistance, the newer cephalosporins may demonstrate activity against certain bacteria such as Enterobacter species, Seratia, and indole-positive Proteus strains, the majority of which are ordinarily resistant to other cephalosporin antibiotics.…”
mentioning
confidence: 99%